Datasets:
Tasks:
Text Generation
Modalities:
Text
Sub-tasks:
language-modeling
Languages:
English
Size:
100K - 1M
License:
:: From Double Loops to Fields | |
:: by Wojciech Skaba and Micha{\l} Muzalewski | |
environ | |
vocabularies XBOOLE_0, ALGSTR_0, CARD_1, SUPINF_2, VECTSP_1, SUBSET_1, | |
RELAT_1, ALGSTR_1, ARYTM_1, ARYTM_3, STRUCT_0, RLVECT_1, BINOP_1, | |
LATTICES, MESFUNC1, GROUP_1, ALGSTR_2, NUMBERS; | |
notations SUBSET_1, XCMPLX_0, ORDINAL1, NUMBERS, REAL_1, STRUCT_0, ALGSTR_0, | |
RLVECT_1, GROUP_1, VECTSP_1, ALGSTR_1; | |
constructors BINOP_2, ALGSTR_1, RLVECT_1, VECTSP_1, MEMBERED, REAL_1, | |
XXREAL_0, NUMBERS, GROUP_1; | |
registrations VECTSP_1, ALGSTR_1, ALGSTR_0, MEMBERED, XREAL_0; | |
requirements SUBSET; | |
theorems VECTSP_1, ALGSTR_1, RLVECT_1, GROUP_1, STRUCT_0, ALGSTR_0, XCMPLX_1; | |
begin :: DOUBLE LOOPS | |
reserve L for non empty doubleLoopStr; | |
Lm1: 0 = 0.F_Real by STRUCT_0:def 6,VECTSP_1:def 5; | |
Lm2: for a,b being Element of F_Real st a<>0.F_Real | |
ex x being Element of F_Real st a*x=b | |
proof | |
let a,b be Element of F_Real such that | |
A1: a<>0.F_Real; | |
reconsider p=a, q=b as Element of REAL by VECTSP_1:def 5; | |
reconsider x = q/p as Element of F_Real by VECTSP_1:def 5; | |
p*(q/p) = q by A1,Lm1,XCMPLX_1:87; | |
then a*x = b; | |
hence thesis; | |
end; | |
Lm3: for a,b being Element of F_Real st a<>0.F_Real ex x being Element of | |
F_Real st x*a=b | |
proof | |
let a,b be Element of F_Real; | |
assume a<>0.F_Real; | |
then ex x being Element of F_Real st a*x=b by Lm2; | |
hence thesis; | |
end; | |
Lm4: ( for a,x,y being Element of F_Real st a<>0.F_Real holds a*x=a*y implies | |
x=y)& for a,x,y being Element of F_Real st a<>0.F_Real holds x*a=y*a implies x= | |
y by VECTSP_1:5; | |
Lm5: ( for a being Element of F_Real holds a*0.F_Real = 0.F_Real)& for a being | |
Element of F_Real holds 0.F_Real*a = 0.F_Real by VECTSP_1:12; | |
:: Below is the basic definition of the mode of DOUBLE LOOP. | |
:: The F_Real example in accordance with the many theorems proved above | |
:: is used to prove the existence. | |
registration | |
cluster F_Real -> multLoop_0-like; | |
coherence by Lm2,Lm3,Lm4,Lm5,ALGSTR_1:16; | |
end; | |
:: In the following part of this article the negation and minus functions | |
:: are defined. This is the only definition of both functions in this article | |
:: while some of their features are independently proved | |
:: for various structures. | |
definition | |
let L be left_add-cancelable add-right-invertible non empty addLoopStr; | |
let a be Element of L; | |
func -a -> Element of L means | |
:Def1: | |
a+it = 0.L; | |
existence by ALGSTR_1:def 4; | |
uniqueness by ALGSTR_0:def 3; | |
end; | |
definition | |
let L be left_add-cancelable add-right-invertible non empty addLoopStr; | |
let a,b be Element of L; | |
func a-b -> Element of L equals | |
a+ -b; | |
correctness; | |
end; | |
registration | |
cluster strict Abelian add-associative commutative associative distributive | |
non degenerated left_zeroed right_zeroed Loop-like well-unital multLoop_0-like | |
for non empty doubleLoopStr; | |
existence | |
proof | |
take F_Real; | |
thus thesis; | |
end; | |
end; | |
definition | |
mode doubleLoop is left_zeroed right_zeroed Loop-like well-unital | |
multLoop_0-like non empty doubleLoopStr; | |
end; | |
definition | |
mode leftQuasi-Field is Abelian add-associative right-distributive non | |
degenerated doubleLoop; | |
end; | |
reserve a,b,c,x,y,z for Element of L; | |
:: The following theorem shows that the basic set of axioms of the | |
:: left quasi-field may be replaced with the following one, | |
:: by just removing a few and adding some other axioms. | |
theorem | |
L is leftQuasi-Field iff (for a holds a + 0.L = a) & (for a ex x st a+ | |
x = 0.L) & (for a,b,c holds (a+b)+c = a+(b+c)) & (for a,b holds a+b = b+a) & 0. | |
L <> 1.L & (for a holds a * 1.L = a) & (for a holds 1.L * a = a) & (for a,b st | |
a<>0.L ex x st a*x=b) & (for a,b st a<>0.L ex x st x*a=b) & (for a,x,y st a<>0. | |
L holds a*x=a*y implies x=y) & (for a,x,y st a<>0.L holds x*a=y*a implies x=y) | |
& (for a holds a*0.L = 0.L) & (for a holds 0.L*a = 0.L) & for a,b,c holds a*(b+ | |
c) = a*b + a*c | |
proof | |
thus L is leftQuasi-Field implies (for a holds a + 0.L = a) & (for a ex x st | |
a+x = 0.L) & (for a,b,c holds (a+b)+c = a+(b+c)) & (for a,b holds a+b = b+a) & | |
0.L <> 1.L & (for a holds a * 1.L = a) & (for a holds 1.L * a = a) & (for a,b | |
st a<>0.L ex x st a*x=b) & (for a,b st a<>0.L ex x st x*a=b) & (for a,x,y st a | |
<>0.L holds a*x=a*y implies x=y) & (for a,x,y st a<>0.L holds x*a=y*a implies x | |
=y) & (for a holds a*0.L = 0.L) & (for a holds 0.L*a = 0.L) & for a,b,c holds a | |
*(b+c) = a*b + a*c by ALGSTR_1:6,16,RLVECT_1:def 2,def 3,def 4,STRUCT_0:def 8 | |
,VECTSP_1:def 2; | |
assume that | |
A1: for a holds a + 0.L = a and | |
A2: for a ex x st a+x = 0.L and | |
A3: for a,b,c holds (a+b)+c = a+(b+c) and | |
A4: for a,b holds a+b = b+a and | |
A5: ( 0.L <> 1.L & for a holds a * 1.L = a )&( ( for a holds 1.L * a = a | |
)& for a, b st a<>0.L ex x st a*x=b ) & ( ( for a,b st a<>0.L ex x st x*a=b)& | |
for a,x,y st a<>0.L holds a*x=a*y implies x=y )&( ( for a,x,y st a<>0.L holds | |
x*a=y*a implies x=y)& for a holds a*0.L = 0.L ) &( ( for a holds 0.L*a = 0.L)& | |
for a,b,c holds a*(b+c) = a*b + a*c); | |
A6: for a holds 0.L + a = a | |
proof | |
let a; | |
thus 0.L + a = a + 0.L by A4 | |
.= a by A1; | |
end; | |
A7: for a,b ex x st a+x=b | |
proof | |
let a,b; | |
consider y such that | |
A8: a+y = 0.L by A2; | |
take x = y+b; | |
thus a+x = 0.L + b by A3,A8 | |
.= b by A6; | |
end; | |
A9: for a,b ex x st x+a=b | |
proof | |
let a,b; | |
consider x such that | |
A10: a+x=b by A7; | |
take x; | |
thus thesis by A4,A10; | |
end; | |
A11: for a,x,y holds a+x=a+y implies x=y | |
proof | |
let a,x,y; | |
consider z such that | |
A12: z+a = 0.L by A1,A2,A3,ALGSTR_1:3; | |
assume a+x = a+y; | |
then (z+a)+x = z+(a+y) by A3 | |
.= (z+a)+y by A3; | |
hence x = 0.L + y by A6,A12 | |
.= y by A6; | |
end; | |
for a,x,y holds x+a=y+a implies x=y | |
proof | |
let a,x,y; | |
assume x+a = y+a; | |
then a+x= y+a by A4 | |
.= a+y by A4; | |
hence thesis by A11; | |
end; | |
hence thesis by A1,A3,A4,A5,A6,A7,A9,A11,ALGSTR_1:6,16,def 2,RLVECT_1:def 2 | |
,def 3,def 4,STRUCT_0:def 8,VECTSP_1:def 2,def 6; | |
end; | |
theorem Th2: | |
for G being Abelian right-distributive doubleLoop, a,b being | |
Element of G holds a*(-b) = -(a*b) | |
proof | |
let G be Abelian right-distributive doubleLoop, a,b be Element of G; | |
a*b + a*(-b) = a*(b+ -b) by VECTSP_1:def 2 | |
.= a*0.G by Def1 | |
.= 0.G by ALGSTR_1:16; | |
hence thesis by Def1; | |
end; | |
theorem Th3: | |
for G being Abelian left_add-cancelable add-right-invertible | |
non empty addLoopStr, a being Element of G holds -(-a) = a | |
proof | |
let G be Abelian left_add-cancelable add-right-invertible non empty | |
addLoopStr, a be Element of G; | |
-a+a = 0.G by Def1; | |
hence thesis by Def1; | |
end; | |
theorem | |
for G being Abelian right-distributive doubleLoop holds (-1.G)*(-1.G) = 1.G | |
proof | |
let G be Abelian right-distributive doubleLoop; | |
thus (-1.G)*(-1.G) = -((-1.G)*1_G) by Th2 | |
.= -(-1.G) | |
.= 1.G by Th3; | |
end; | |
theorem | |
for G being Abelian right-distributive doubleLoop, a,x,y being Element | |
of G holds a*(x-y) = a*x - a*y | |
proof | |
let G be Abelian right-distributive doubleLoop, a,x,y be Element of G; | |
thus a*(x-y) = a*x + a*(-y) by VECTSP_1:def 2 | |
.= a*x - a*y by Th2; | |
end; | |
:: RIGHT QUASI-FIELD | |
:: The next contemplated algebraic structure is so called right quasi-field. | |
:: This structure is defined as a DOUBLE LOOP augmented with three axioms. | |
:: The reasoning is similar to that of left quasi-field. | |
definition | |
mode rightQuasi-Field is Abelian add-associative left-distributive non | |
degenerated doubleLoop; | |
end; | |
theorem | |
L is rightQuasi-Field iff (for a holds a + 0.L = a) & (for a ex x st a | |
+x = 0.L) & (for a,b,c holds (a+b)+c = a+(b+c)) & (for a,b holds a+b = b+a) & | |
0.L <> 1.L & (for a holds a * 1.L = a) & (for a holds 1.L * a = a) & (for a,b | |
st a<>0.L ex x st a*x=b) & (for a,b st a<>0.L ex x st x*a=b) & (for a,x,y st a | |
<>0.L holds a*x=a*y implies x=y) & (for a,x,y st a<>0.L holds x*a=y*a implies x | |
=y) & (for a holds a*0.L = 0.L) & (for a holds 0.L*a = 0.L) & for a,b,c holds ( | |
b+c)*a = b*a + c*a | |
proof | |
thus L is rightQuasi-Field implies (for a holds a + 0.L = a) & (for a ex x | |
st a+x = 0.L) & (for a,b,c holds (a+b)+c = a+(b+c)) & (for a,b holds a+b = b+a) | |
& 0.L <> 1.L & (for a holds a * 1.L = a) & (for a holds 1.L * a = a) & (for a,b | |
st a<>0.L ex x st a*x=b) & (for a,b st a<>0.L ex x st x*a=b) & (for a,x,y st a | |
<>0.L holds a*x=a*y implies x=y) & (for a,x,y st a<>0.L holds x*a=y*a implies x | |
=y) & (for a holds a*0.L = 0.L) & (for a holds 0.L*a = 0.L) & for a,b,c holds ( | |
b+c)*a = b*a + c*a by ALGSTR_1:6,16,RLVECT_1:def 2,def 3,def 4,STRUCT_0:def 8 | |
,VECTSP_1:def 3; | |
assume that | |
A1: for a holds a + 0.L = a and | |
A2: for a ex x st a+x = 0.L and | |
A3: for a,b,c holds (a+b)+c = a+(b+c) and | |
A4: for a,b holds a+b = b+a and | |
A5: ( 0.L <> 1.L & for a holds a * 1.L = a )&( ( for a holds 1.L * a = a | |
)& for a, b st a<>0.L ex x st a*x=b ) & ( ( for a,b st a<>0.L ex x st x*a=b)& | |
for a,x,y st a<>0.L holds a*x=a*y implies x=y )&( ( for a,x,y st a<>0.L holds | |
x*a=y*a implies x=y)& for a holds a*0.L = 0.L ) &( ( for a holds 0.L*a = 0.L)& | |
for a,b,c holds (b+c)*a = b*a + c*a); | |
A6: for a,b ex x st x+a=b | |
proof | |
let a,b; | |
consider y such that | |
A7: y+a = 0.L by A1,A2,A3,ALGSTR_1:3; | |
take x = b+y; | |
thus x+a = b + 0.L by A3,A7 | |
.= b by A1; | |
end; | |
A8: for a holds 0.L + a = a | |
proof | |
let a; | |
thus 0.L + a = a + 0.L by A4 | |
.= a by A1; | |
end; | |
A9: for a,x,y holds a+x=a+y implies x=y | |
proof | |
let a,x,y; | |
consider z such that | |
A10: z+a = 0.L by A1,A2,A3,ALGSTR_1:3; | |
assume a+x = a+y; | |
then (z+a)+x = z+(a+y) by A3 | |
.= (z+a)+y by A3; | |
hence x = 0.L + y by A8,A10 | |
.= y by A8; | |
end; | |
A11: for a,x,y holds x+a=y+a implies x=y | |
proof | |
let a,x,y; | |
consider z such that | |
A12: a+z = 0.L by A2; | |
assume x+a = y+a; | |
then x+(a+z) = (y+a)+z by A3 | |
.= y+(a+z) by A3; | |
hence x = y + 0.L by A1,A12 | |
.= y by A1; | |
end; | |
for a,b ex x st a+x=b | |
proof | |
let a,b; | |
consider y such that | |
A13: a+y = 0.L by A2; | |
take x = y+b; | |
thus a+x = 0.L + b by A3,A13 | |
.= b by A8; | |
end; | |
hence thesis by A1,A3,A4,A5,A8,A6,A9,A11,ALGSTR_1:6,16,def 2,RLVECT_1:def 2 | |
,def 3,def 4,STRUCT_0:def 8,VECTSP_1:def 3,def 6; | |
end; | |
:: Below, the three features concerned with the - function, | |
:: numbered 20..22 are proved. Where necessary, a few additional | |
:: facts are included. They are independent of the similar proofs | |
:: performed for the left quasi-field. | |
reserve G for left-distributive doubleLoop, | |
a,b,x,y for Element of G; | |
theorem Th7: | |
(-b)*a = -(b*a) | |
proof | |
b*a + (-b)*a = (b+(-b))*a by VECTSP_1:def 3 | |
.= 0.G*a by Def1 | |
.= 0.G by ALGSTR_1:16; | |
hence thesis by Def1; | |
end; | |
theorem | |
for G being Abelian left-distributive doubleLoop holds (-1.G)*(-1.G) = 1.G | |
proof | |
let G be Abelian left-distributive doubleLoop; | |
thus (-1.G)*(-1.G) = -(1_G*(-1.G)) by Th7 | |
.= -(-1.G) | |
.= 1.G by Th3; | |
end; | |
theorem | |
(x-y)*a = x*a - y*a | |
proof | |
thus (x-y)*a = x*a + (-y)*a by VECTSP_1:def 3 | |
.= x*a - y*a by Th7; | |
end; | |
:: DOUBLE SIDED QUASI-FIELD | |
:: The next contemplated algebraic structure is so called double sided | |
:: quasi-field. This structure is also defined as a DOUBLE LOOP augmented | |
:: with four axioms, while its relevance to left/right quasi-field is | |
:: independently contemplated. | |
:: The reasoning is similar to that of left/right quasi-field. | |
definition | |
mode doublesidedQuasi-Field is Abelian add-associative distributive non | |
degenerated doubleLoop; | |
end; | |
reserve a,b,c,x,y,z for Element of L; | |
theorem | |
L is doublesidedQuasi-Field iff (for a holds a + 0.L = a) & (for a ex | |
x st a+x = 0.L) & (for a,b,c holds (a+b)+c = a+(b+c)) & (for a,b holds a+b = b+ | |
a) & 0.L <> 1.L & (for a holds a * 1.L = a) & (for a holds 1.L * a = a) & (for | |
a,b st a<>0.L ex x st a*x=b) & (for a,b st a<>0.L ex x st x*a=b) & (for a,x,y | |
st a<>0.L holds a*x=a*y implies x=y) & (for a,x,y st a<>0.L holds x*a=y*a | |
implies x=y) & (for a holds a*0.L = 0.L) & (for a holds 0.L*a = 0.L) & (for a,b | |
,c holds a*(b+c) = a*b + a*c) & for a,b,c holds (b+c)*a = b*a + c*a | |
proof | |
thus L is doublesidedQuasi-Field implies (for a holds a + 0.L = a) & (for a | |
ex x st a+x = 0.L) & (for a,b,c holds (a+b)+c = a+(b+c)) & (for a,b holds a+b = | |
b+a) & 0.L <> 1.L & (for a holds a * 1.L = a) & (for a holds 1.L * a = a) & ( | |
for a,b st a<>0.L ex x st a*x=b) & (for a,b st a<>0.L ex x st x*a=b) & (for a,x | |
,y st a<>0.L holds a*x=a*y implies x=y) & (for a,x,y st a<>0.L holds x*a=y*a | |
implies x=y) & (for a holds a*0.L = 0.L) & (for a holds 0.L*a = 0.L) & (for a,b | |
,c holds a*(b+c) = a*b + a*c) & for a,b,c holds (b+c)*a = b*a + c*a by | |
ALGSTR_1:6,16,RLVECT_1:def 2,def 3,def 4,STRUCT_0:def 8,VECTSP_1:def 7; | |
assume that | |
A1: for a holds a + 0.L = a and | |
A2: for a ex x st a+x = 0.L and | |
A3: for a,b,c holds (a+b)+c = a+(b+c) and | |
A4: for a,b holds a+b = b+a and | |
A5: ( 0.L <> 1.L & for a holds a * 1.L = a )&( ( for a holds 1.L * a = a | |
)& for a, b st a<>0.L ex x st a*x=b ) & ( ( for a,b st a<>0.L ex x st x*a=b)& | |
for a,x,y st a<>0.L holds a*x=a*y implies x=y )&( ( for a,x,y st a<>0.L holds | |
x*a=y*a implies x=y)& for a holds a*0.L = 0.L ) &( ( ( for a holds 0.L*a = 0.L) | |
& for a,b,c holds a*(b+c) = a*b + a*c )& for a,b, c holds (b+c)*a = b*a + c*a); | |
A6: for a,b ex x st x+a=b | |
proof | |
let a,b; | |
consider y such that | |
A7: y+a = 0.L by A1,A2,A3,ALGSTR_1:3; | |
take x = b+y; | |
thus x+a = b + 0.L by A3,A7 | |
.= b by A1; | |
end; | |
A8: for a holds 0.L + a = a | |
proof | |
let a; | |
thus 0.L + a = a + 0.L by A4 | |
.= a by A1; | |
end; | |
A9: for a,x,y holds a+x=a+y implies x=y | |
proof | |
let a,x,y; | |
consider z such that | |
A10: z+a = 0.L by A1,A2,A3,ALGSTR_1:3; | |
assume a+x = a+y; | |
then (z+a)+x = z+(a+y) by A3 | |
.= (z+a)+y by A3; | |
hence x = 0.L + y by A8,A10 | |
.= y by A8; | |
end; | |
A11: for a,x,y holds x+a=y+a implies x=y | |
proof | |
let a,x,y; | |
consider z such that | |
A12: a+z = 0.L by A2; | |
assume x+a = y+a; | |
then x+(a+z) = (y+a)+z by A3 | |
.= y+(a+z) by A3; | |
hence x = y + 0.L by A1,A12 | |
.= y by A1; | |
end; | |
for a,b ex x st a+x=b | |
proof | |
let a,b; | |
consider y such that | |
A13: a+y = 0.L by A2; | |
take x = y+b; | |
thus a+x = 0.L + b by A3,A13 | |
.= b by A8; | |
end; | |
hence thesis by A1,A3,A4,A5,A8,A6,A9,A11,ALGSTR_1:6,16,def 2,RLVECT_1:def 2 | |
,def 3,def 4,STRUCT_0:def 8,VECTSP_1:def 6,def 7; | |
end; | |
:: SKEW FIELD | |
:: A Skew-Field is defined as a double sided quasi-field extended | |
:: with the associativity of multiplication. | |
definition | |
mode _Skew-Field is associative doublesidedQuasi-Field; | |
end; | |
Lm6: 0.L <> 1.L & (for a holds a * 1.L = a) & (for a st a<>0.L ex x st a*x = | |
1.L) & (for a,b,c holds (a*b)*c = a*(b*c)) & (for a holds a*0.L = 0.L) implies | |
(a*b = 1.L implies b*a = 1.L) | |
proof | |
assume that | |
A1: 0.L <> 1.L and | |
A2: for a holds a * 1.L = a and | |
A3: for a st a<>0.L ex x st a*x = 1.L and | |
A4: for a,b,c holds (a*b)*c = a*(b*c) and | |
A5: for a holds a*0.L = 0.L; | |
thus a*b = 1.L implies b*a = 1.L | |
proof | |
assume | |
A6: a*b = 1.L; | |
then b<>0.L by A1,A5; | |
then consider x such that | |
A7: b * x = 1.L by A3; | |
thus b*a = (b*a) * (b*x) by A2,A7 | |
.= ((b*a) * b) * x by A4 | |
.= (b * 1.L) * x by A4,A6 | |
.= 1.L by A2,A7; | |
end; | |
end; | |
Lm7: 0.L <> 1.L & (for a holds a * 1.L = a) & (for a st a<>0.L ex x st a*x = | |
1.L) & (for a,b,c holds (a*b)*c = a*(b*c)) & (for a holds a*0.L = 0.L) implies | |
1.L*a = a*1.L | |
proof | |
assume that | |
A1: 0.L <> 1.L and | |
A2: for a holds a * 1.L = a and | |
A3: for a st a<>0.L ex x st a*x = 1.L and | |
A4: for a,b,c holds (a*b)*c = a*(b*c) and | |
A5: for a holds a*0.L = 0.L; | |
A6: a<>0.L implies 1.L*a = a*1.L | |
proof | |
assume a<>0.L; | |
then consider x such that | |
A7: a * x = 1.L by A3; | |
thus 1.L*a = a * (x*a) by A4,A7 | |
.= a*1.L by A1,A2,A3,A4,A5,A7,Lm6; | |
end; | |
a=0.L implies 1.L*a = a*1.L | |
proof | |
assume | |
A8: a=0.L; | |
hence 1.L*a = 0.L by A5 | |
.= a*1.L by A2,A8; | |
end; | |
hence thesis by A6; | |
end; | |
Lm8: 0.L <> 1.L & (for a holds a * 1.L = a) & (for a st a<>0.L ex x st a*x = | |
1.L) & (for a,b,c holds (a*b)*c = a*(b*c)) & (for a holds a*0.L = 0.L) implies | |
for a st a<>0.L ex x st x*a = 1.L | |
proof | |
assume that | |
A1: 0.L <> 1.L & for a holds a * 1.L = a and | |
A2: for a st a<>0.L ex x st a*x = 1.L and | |
A3: ( for a,b,c holds (a*b)*c = a*(b*c))& for a holds a*0.L = 0.L; | |
let a; | |
assume a<>0.L; | |
then consider x such that | |
A4: a * x = 1.L by A2; | |
x*a=1.L by A1,A2,A3,A4,Lm6; | |
hence thesis; | |
end; | |
:: The following theorem shows that the basic set of axioms of the | |
:: skew field may be replaced with the following one, | |
:: by just removing a few and adding some other axioms. | |
:: A few theorems proved earlier are highly utilized. | |
theorem Th11: | |
L is _Skew-Field iff (for a holds a + 0.L = a) & (for a ex x st a+x = 0.L) | |
& (for a,b,c holds (a+b)+c = a+(b+c)) & (for a,b holds a+b = b+a) | |
& 0.L <> 1.L & (for a holds a * 1.L = a) | |
& (for a st a<>0.L ex x st a*x = 1.L) & (for a holds a*0.L = 0.L) | |
& (for a holds 0.L*a = 0.L) & (for a,b,c holds (a*b)*c = a*(b*c)) | |
& (for a,b,c holds a*(b+c) = a*b + a*c) | |
& (for a,b,c holds (b+c)*a = b*a + c*a) | |
proof | |
thus L is _Skew-Field implies (for a holds a + 0.L = a) | |
& (for a ex x st a+x = 0.L) & (for a,b,c holds (a+b)+c = a+(b+c)) | |
& (for a,b holds a+b = b+a) & 0.L <> 1.L & (for a holds a * 1.L = a) | |
& (for a st a<>0.L ex x st a*x = 1.L) & (for a holds a*0.L = 0.L) | |
& (for a holds 0.L*a = 0.L) & (for a,b,c holds (a*b)*c = a*(b*c)) | |
& (for a,b,c holds a*(b+c) = a*b + a*c) | |
& (for a,b,c holds (b+c)*a = b*a + c*a) by ALGSTR_1:6,16,GROUP_1:def 3 | |
,RLVECT_1:def 2,def 3,def 4,STRUCT_0:def 8,VECTSP_1:def 7; | |
assume | |
A1: (for a holds a + 0.L = a) & (for a ex x st a+x = 0.L) | |
& (for a,b,c holds (a+b)+c = a+(b+c)) & (for a,b holds a+b = b+a) | |
& 0.L <> 1.L & (for a holds a * 1.L = a) | |
& (for a st a<>0.L ex x st a*x = 1.L) & (for a holds a*0.L = 0.L) | |
& (for a holds 0.L*a = 0.L) & (for a,b,c holds (a*b)*c = a*(b*c)) | |
& (for a,b,c holds a*(b+c) = a*b + a*c) | |
& (for a,b,c holds (b+c)*a = b*a + c*a); | |
now thus | |
A2: for a holds 0.L + a = a | |
proof | |
let a; | |
thus 0.L + a = a + 0.L by A1 | |
.= a by A1; | |
end; | |
thus for a,b ex x st a+x=b | |
proof | |
let a,b; | |
consider y such that | |
A3: a+y = 0.L by A1; | |
take x = y+b; | |
thus a+x = 0.L + b by A1,A3 | |
.= b by A2; | |
end; | |
thus for a,b ex x st x+a=b | |
proof | |
let a,b; | |
consider y such that | |
A4: y+a = 0.L by A1,ALGSTR_1:3; | |
take x = b+y; | |
thus x+a = b + 0.L by A1,A4 | |
.= b by A1; | |
end; | |
thus for a,x,y holds a+x=a+y implies x=y | |
proof | |
let a,x,y; | |
consider z such that | |
A5: z+a = 0.L by A1,ALGSTR_1:3; | |
assume a+x = a+y; | |
then (z+a)+x = z+(a+y) by A1 | |
.= (z+a)+y by A1; | |
hence x = 0.L + y by A2,A5 | |
.= y by A2; | |
end; | |
thus for a,x,y holds x+a=y+a implies x=y | |
proof | |
let a,x,y; | |
consider z such that | |
A6: a+z = 0.L by A1; | |
assume x+a = y+a; | |
then x+(a+z) = (y+a)+z by A1 | |
.= y+(a+z) by A1; | |
hence x = y + 0.L by A1,A6 | |
.= y by A1; | |
end; thus | |
A7: for a holds 1.L * a = a | |
proof | |
let a; | |
thus 1.L*a = a*1.L by A1,Lm7 | |
.= a by A1; | |
end; | |
thus for a,b st a<>0.L ex x st a*x=b | |
proof | |
let a,b; | |
assume a<>0.L; | |
then consider y such that | |
A8: a*y = 1.L by A1; | |
take x = y*b; | |
thus a*x = 1.L * b by A1,A8 | |
.= b by A7; | |
end; | |
thus for a,b st a<>0.L ex x st x*a=b | |
proof | |
let a,b; | |
assume a<>0.L; | |
then consider y such that | |
A9: y*a = 1.L by A1,Lm8; | |
take x = b*y; | |
thus x*a = b * 1.L by A1,A9 | |
.= b by A1; | |
end; | |
thus for a,x,y st a<>0.L holds a*x=a*y implies x=y | |
proof | |
let a,x,y; | |
assume a<>0.L; | |
then consider z such that | |
A10: z*a = 1.L by A1,Lm8; | |
assume a*x = a*y; | |
then (z*a)*x = z*(a*y) by A1 | |
.= (z*a)*y by A1; | |
hence x = 1.L * y by A7,A10 | |
.= y by A7; | |
end; | |
thus for a,x,y st a<>0.L holds x*a=y*a implies x=y | |
proof | |
let a,x,y; | |
assume a<>0.L; | |
then consider z such that | |
A11: a*z = 1.L by A1; | |
assume x*a = y*a; | |
then x*(a*z) = (y*a)*z by A1 | |
.= y*(a*z) by A1; | |
hence x = y * 1.L by A1,A11 | |
.= y by A1; | |
end; | |
end; | |
hence thesis by A1,ALGSTR_1:6,16,def 2,GROUP_1:def 3,RLVECT_1:def 2,def 3 | |
,def 4,STRUCT_0:def 8,VECTSP_1:def 6,def 7; | |
end; | |
:: FIELD | |
:: A _Field is defined as a Skew-Field with the axiom of the commutativity | |
:: of multiplication. | |
definition | |
mode _Field is commutative _Skew-Field; | |
end; | |
theorem | |
L is _Field iff (for a holds a + 0.L = a) & (for a ex x st a+x = 0.L) | |
& (for a,b,c holds (a+b)+c = a+(b+c)) & (for a,b holds a+b = b+a) & 0.L <> 1.L | |
& (for a holds a * 1.L = a) & (for a st a<>0.L ex x st a*x = 1.L) & (for a | |
holds a*0.L = 0.L) & (for a,b,c holds (a*b)*c = a*(b*c)) & (for a,b,c holds a*( | |
b+c) = a*b + a*c) & for a,b holds a*b = b*a | |
proof | |
thus L is _Field implies (for a holds a + 0.L = a) & (for a ex x st a+x = 0. | |
L) & (for a,b,c holds (a+b)+c = a+(b+c)) & (for a,b holds a+b = b+a) & 0.L <> | |
1.L & (for a holds a * 1.L = a) & (for a st a<>0.L ex x st a*x = 1.L) & (for a | |
holds a*0.L = 0.L) & (for a,b,c holds (a*b)*c = a*(b*c)) & (for a,b,c holds a*( | |
b+c) = a*b + a*c) & for a,b holds a*b = b*a by Th11,GROUP_1:def 12; | |
assume that | |
A1: ( ( for a holds a + 0.L = a)& for a ex x st a+x = 0.L )&( ( for a,b, | |
c holds ( a +b)+c = a+(b+c))& for a,b holds a+b = b+a ) &( ( 0.L <> 1.L & for a | |
holds a * 1.L = a )& for a st a<>0.L ex x st a*x = 1.L ) and | |
A2: for a holds a*0.L = 0.L and | |
A3: for a,b,c holds (a*b)*c = a*(b*c) and | |
A4: for a,b,c holds a*(b+c) = a*b + a*c and | |
A5: for a,b holds a*b = b*a; | |
A6: for a holds 0.L*a = 0.L | |
proof | |
let a; | |
thus 0.L*a = a*0.L by A5 | |
.= 0.L by A2; | |
end; | |
for a,b,c holds (b+c)*a = b*a + c*a | |
proof | |
let a,b,c; | |
thus (b+c)*a = a*(b+c) by A5 | |
.= a*b + a*c by A4 | |
.= b*a + a*c by A5 | |
.= b*a + c*a by A5; | |
end; | |
hence thesis by A1,A2,A3,A4,A5,A6,Th11,GROUP_1:def 12; | |
end; | |